Case report: Peritumoral hepatic steatosis in a patient with a metastatic somatostatin-producing oligosymptomatic neuroendocrine neoplasm - Shao, Yuming; Gui, Yang; Cheng, Yuejuan; Xu, Jia; Chang, Xiaoyan; Lv, Ke (Frontiers in Oncology, 2022)
Neuroendocrine neoplasms (NENs) comprise a heterogeneous collection of tumors derived from various neuroendocrine cells and are divided into functioning NEN and non-functioning NEN. Some NENs present with mild symptoms and can secrete somatostatin. These neoplasms are known as somatostatin-producing oligosymptomatic NENs. In this report, we describe a case of metastatic somatostatin-producing oligosymptomatic NEN with peritumoral hepatic steatosis and review the relevant literature. The patient was a 45-year-old woman who presented with mild steatorrhea and melena. A computed tomography scan revealed an enlarged pancreas protruding into the duodenum. Pathology after total pancreatectomy showed a grade 2 pancreatic NEN with positive somatostatin immunostaining. Enlarging masses on the liver were observed after the operation. Ultrasound examination revealed several lesions in the liver, with inner hypoechoic areas that showed rapid enhancement and fast washout on contrast-enhanced ultrasonography and outer hyperechoic areas with continuous iso-enhancement. Therefore, the inner hypoechoic areas seen on contrast-enhanced ultrasonography were suspected to be true metastases. A biopsy confirmed this suspicion and indicated that the outer areas were peritumoral liver steatosis. This case highlights the importance of the imaging pattern described in this report for accurate diagnosis of metastatic NEN to avoid incorrect estimation of tumor size or a missed diagnosis on biopsy.